2017
DOI: 10.3389/fpls.2017.00978
|View full text |Cite
|
Sign up to set email alerts
|

The CBL and CIPK Gene Family in Grapevine (Vitis vinifera): Genome-Wide Analysis and Expression Profiles in Response to Various Abiotic Stresses

Abstract: Calcium plays a central role in regulating signal transduction pathways. Calcineurin B-like proteins (CBLs), which harbor a crucial region consisting of EF hands that capture Ca2+, interact in a specific manner with CBL-interacting protein kinases (CIPKs). This two gene families or their interacting-complex widely respond to various environment stimuli and development processes. The genome-wide annotation and specific expression patterns of CBLs and CIPKs, however, in grapevine remain unclear. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 60 publications
(95 reference statements)
11
90
0
Order By: Relevance
“…Following the identification of 26 CIPK family genes in Arabidopsis thaliana genome [9], CIPK genes in many plant species have also been identified by genome-wide analyses of their genomes. For example, there are 34 in rice (Oryza sativa) [10], 43 in maize (Zea mays) [11], 27 in poplar (Populus tremula) [12], 23 in Brassica napus [13], 52 in soybean (Glycine max) [14], 20 in Vitis vinifera [15], 34 in apple (Malus domestica) [16], and 16 CIPKs in Prunus mume [17]. These studies reported that the CIPK gene family can be classified into two groups, including an exon-rich group and exon-poor group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the identification of 26 CIPK family genes in Arabidopsis thaliana genome [9], CIPK genes in many plant species have also been identified by genome-wide analyses of their genomes. For example, there are 34 in rice (Oryza sativa) [10], 43 in maize (Zea mays) [11], 27 in poplar (Populus tremula) [12], 23 in Brassica napus [13], 52 in soybean (Glycine max) [14], 20 in Vitis vinifera [15], 34 in apple (Malus domestica) [16], and 16 CIPKs in Prunus mume [17]. These studies reported that the CIPK gene family can be classified into two groups, including an exon-rich group and exon-poor group.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported that the CIPK gene family can be classified into two groups, including an exon-rich group and exon-poor group. It was reported that CIPK genes participate in plant growth and development, and play critical roles in various stresses, including abiotic stresses and hormones [15,18]. The expression levels of CIPK genes in G. raimondii and G. arboreum were induced under abiotic stresses (drought, salt and low temperature) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our results on CIPKs confirm that this gene family in plants is larger compared to CBL. Indeed, we identified 26 CIPKs in the three potato genomes analyzed, 20, 26, and 30 CIPKs were found in Vitis, Arabidopsis, and rice, respectively (Kolukisaoglu et al 2004, Kanvar et al 2014, Xi et al 2017. These findings indicate that gene duplication events, such as segmental and/or tandem duplications might play a significant role in their expansion.…”
Section: Discussionmentioning
confidence: 64%
“…Our results indicate that both CBL and CIPK genes originate from tandem duplication events. In contrast, Xi et al (2017) reported that 50 % of VvCBLs and 40 % of VvCIPKs arise by tandem duplication, and 25 % of VvCIPKs are derived from segmental duplications in V. vinifera. Our phylogenetic analysis provided evidence that variability in the number of paralogs within different potato species were present.…”
Section: Discussionmentioning
confidence: 94%
“…The availability of a large number of sequenced plant genomes has allowed analysis of the complexity, conservation and evolution of CBL and CIPK signaling network. (Kolukisaoglu et al, 2004;Yu et al, 2007;Zhang et al, 2008;Weinl and Kudla, 2009;Piao et al, 2010;Chen et al, 2011;Lyzenga et al, 2013;Zhang et al, 2014;Sun et al, 2015;Li et al, 2016;Yin et al, 2017;Xi et al, 2017;Mo et al, 2018;Mohanta et al, 2015;Niu et al, 2018). In addition, the genome sequences for algae and non-vascular plants have also enabled us to address the evolutionary aspects of this signaling network.…”
Section: Evolutionary Analysis Of the Cbl-cipk Signaling Networkmentioning
confidence: 99%